Identification of Amylase-Producing Thermophilic Bacteria through 16sRNA Gene Analysis: MGH3 Strain - Ruth Rize Paas Megahati (Jurnal Penelitian Pendidikan IPA, 2023)
Thermostable amylase plays a role in the industrial sector because it is resistant to high temperatures, has high enzyme activity in various parameters and is economical in production costs. The thermostable amylase used in industry is stable and thermo activity. Bacteria that produce thermostable amylase can come from hot springs with temperatures above 80Â°C, such as Semurup hot springs, Kerinci, Jambi province, Indonesia. Semurup hot spring (Jambi) has a temperature of 82Â°C and a pH of 8.6. This causes variations in the content of organic, inorganic, and mineral compounds in the Semurup hot springs. The varied mineral content causes thermophilic bacteria to survive and the genetic diversity of thermophilic bacteria varies. This study aimed to molecularly identify thermostable amylase-producing thermophilic bacteria by analyzing the 16sRNA gene. Identification of bacteria was carried out by analyzing the 16S rRNA gene of thermophilic bacteria, such as DNA Isolation, DNA Amplification, 16S rRNA Gene Analysis, Alignment, and Phylogenetic Tree. There were 4 different bases between the bacterial isolates MGH3 and Bacillus licheniformis ATCC 14580, namely bases no. 87, 120, 967, and 1374. The difference of 4 bases in the two bacterial isolates already shows that the two isolates have a close kinship. So, most likely the MGH3 bacterial isolate is Bacillus licheniformis strain MGH3.